Inhibition of T4 Bacteriophage Multiplication by Superinfecting Ghosts and the Development of Tolerance After Bacteriophage Infection - Duckworth, Donna Hardy (1971)
Simultaneous addition of T4 phage and ghosts to host cells prevents infective center formation. Cells which have been infected with phage for less than 2 min are also inhibited by superinfecting ghosts. After this time, a chloramphenicol-inhibitable reaction occurs which causes the phage-infected cells to become increasingly tolerant of added ghosts.